2020
DOI: 10.1002/anie.202000062
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective and Site‐Selective Lysine‐Directed Lysine Modification Enables Single‐Site Labeling of Native Proteins

Abstract: The necessity for precision labeling of proteins emerged during the efforts to understand and regulate their structure and function. It demands selective attachment of tags such as affinity probes, fluorophores, and potent cytotoxins. Here, we report a method that enables single‐site labeling of a high‐frequency Lys residue in the native proteins. At first, the enabling reagent forms stabilized imines with multiple solvent‐accessible Lys residues chemoselectively. These linchpins create the opportunity to regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 54 publications
(4 reference statements)
1
65
0
Order By: Relevance
“…[11][12][13] In parallel, site-selective chemical strategies for the conjugation of native and natural proteins have also flourishedo ver the past few years, giving rise to methods targeting varioust ypes of amino acids (for example, lysine, cysteine, tryptophan, tyrosine) that proved to be effective on proteins of all sizes, including antibodies. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] With the aim of pursuing the efforts in this field, we could not help but notice that the vast majority of previously reported strategies for the site-selective conjugation of native proteins were focusedo nt he modificationo faunique residue. We hypothesized that targeting two different amino acid side chainss imultaneously would lower the enormouss ubset of possibilities given by single-residue bioconjugation techniques, thus increasing our chances of developing as ite-selective method by minimising the number of potentially reactive sites;apath that has also been successfully explored by others in the meantime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] In parallel, site-selective chemical strategies for the conjugation of native and natural proteins have also flourishedo ver the past few years, giving rise to methods targeting varioust ypes of amino acids (for example, lysine, cysteine, tryptophan, tyrosine) that proved to be effective on proteins of all sizes, including antibodies. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] With the aim of pursuing the efforts in this field, we could not help but notice that the vast majority of previously reported strategies for the site-selective conjugation of native proteins were focusedo nt he modificationo faunique residue. We hypothesized that targeting two different amino acid side chainss imultaneously would lower the enormouss ubset of possibilities given by single-residue bioconjugation techniques, thus increasing our chances of developing as ite-selective method by minimising the number of potentially reactive sites;apath that has also been successfully explored by others in the meantime.…”
Section: Introductionmentioning
confidence: 99%
“…Regioselective (i.e., site‐specific) methods were thus developed and are currently dominated by the use of recombinant proteins, incorporating exogenous amino acid residues (natural or unnatural) or peptide sequences that can be specifically targeted by a tailored reagent or strategy [11–13] . In parallel, site‐selective chemical strategies for the conjugation of native and natural proteins have also flourished over the past few years, giving rise to methods targeting various types of amino acids (for example, lysine, cysteine, tryptophan, tyrosine) that proved to be effective on proteins of all sizes, including antibodies [14–28] …”
Section: Introductionmentioning
confidence: 99%
“…Analysis of crystal structures of Fab domains of Rituximab, Cetuximab and Belimumab showed that these labelling sites indeed have a nearby lysine residue in the 3D structure (Supporting information Figure S19–S21). We know from earlier studies, using the same salicylaldehyde guiding moiety for protein labeling, that labeling of the LC was also observed [26] . We were however, pleased to see that for the LDLR 1 a reagent most sites were located on the HC (Data shown in Supporting information pages S14–16).…”
Section: Resultsmentioning
confidence: 68%
“…In other studies, mentioned above, where the same guiding moiety is used, much harsher conditions were required with up to 25 equiv. of reagent and in some cases 20 % DMSO [25, 26] . Furthermore, the labeling from the LDLR 1 a occurred predominantly once on the heavy chain.…”
Section: Resultsmentioning
confidence: 96%
“…14A). 224 2.6.3 Selective arginine modification. The lower abundance of arginine residues in native antibodies compared to lysine residues makes arginine-selective modification attractive for the preparation of homogeneous conjugates.…”
Section: C-/n-terminal Modificationsmentioning
confidence: 99%